Verification and Moral Values in Diwam Ibnu Adim: A Study of the Science of Arudh - Setiawan, Shafira Nandya; Rohanda; Halim, M. Abdul (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to analyze the versification (science of 'arudh) and moral values in Diwan Ibn al-Adim. The focus of this study includes identifying the types of bahar and zihaf used in the composition of the verses of the poem and the disclosure of the moral values ??contained therein. This study uses a qualitative descriptive method, combining the arudh science approach to analyze the structure of the poem's meter and the Islamic moral studies approach to interpret the moral messages of literary works. The research data sources are selected verses of poetry from Diwan Ibn al-Adim obtained through the Diwanul al-‘Arabi application. The data were analyzed through the following stages: (1) classification of the verses of the poem, (2) analysis of the wazan, taf'ilah, and bahar patterns according to the theory of science of 'arudh, and (3) interpretation of the content of moral values ??contained in the text. The results of the study show that Diwan Ibn al-'Adim is dominated by the use of bahar Basith, Thawîl, and Kamil with variations of zihaf such as khaban, qabdh, and idhmar. From a moral perspective, various values are found, such as tawadhu, sabar, jujur, iffah, wara, hikmah, zuhud, generosity, responsibility, and piety. In addition, this work contains moral messages on human relations with Allah SWT, fellow humans, and the social environment. This study concludes that Diwan Ibn al-'Adim is a literary work not only aesthetically superior, with a strong poetic structure, but also rich in moral education relevant throughout time. These findings are expected to contribute to the development of Arabic literary studies, especially those that integrate aspects of form and value.